KAJIAN ELEMEN-ELEMEN PENENTU KEBERHASILAN KEMUNGKINAN PENERAPAN TRANSIT ORIENTED DEVELOPMENT (TOD) DI KAWASAN BANYUMANIK KOTA SEMARANG - T, Nograito Wimardana (Jurusan Perencanaan Wilayah dan Kota, 2013)
Transit Oriented Development (TOD) is a concept of developing an integrated transportation system Â with land use. Implementation of TOD in the Banyumanik Area, aims to address the impacts of urban sprawl, namely traffic congestion, air pollution, consumption of open space, and a sense of kinship society in a modern residential neighborhood. Based on TOD best practices, elements that influential and become critical success of TOD implementation are land use, hinterland areas support, transportation systems, the role of stakeholders, and the level of understanding and public acceptance. This study aims to identify and know the priority of elements and components that influence and become a critical success for possible TOD applications in the Banyumanik Area. This study used Delphi Method with four expert informants as respondents. The results showed that TOD concept has a potential to be applied in the Banyumanik Area. In order to TOD application can be run effectively and achieve its objectives, there are six elements and eighteen components that need an attention. Eighteen components are part of the six elements. Elements and components also need to be prioritized according to level of importance. The order of priority elements, namely the role and collaboration between stakeholders, the level of understanding and public acceptance, regulatory systems, land use, transportation systems, and hinterland areas support. Elements and components that obtained has evolved from the synthesis of literature review. Recommendations can be given is development actors and citizens must begin to play an active role seriously and collaborate in formulating a regulatory system which is a guidelines of TOD implementation in the Banyumanik Area. Along with this, the level of understanding and public acceptance (especially local) of this concept should be developed because the people adaptation to something new is different, so it will takes time for the TOD concept can be embedded within them as a solution to solve the Â transportation problem,